2022
DOI: 10.33259/jlivestsci.2022.1-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of enzyme preparations and lecithin on the blood picture of laying hens

Abstract: The use of new feed factors in poultry feeding is necessarily reflected in the change in blood parameters. The article presents the results of physiological studies on the study of changes in the hematological parameters of laying hens with the additional use of enzyme preparations Sanzaym and Sanfayz 5000, as well as lecithin in their feeding. Scientific and economic experience, during which the main physiological indicators were studied, was carried out in the State Unitary Enterprise of the Breeding Reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…The blood content of triglycerides and cholesterol is one of the important indicators that characterize the production of eggs in laying hens, and their accumulation in the blood is at high levels (higher than normal rates in the blood), It can be considered evidence of a decrease in the efficiency of using nutrients, especially fats, as a result of oxidative stress at the same time, a sharp decrease can be considered an indication of atrophy in the liver, or acute poisoning [32], This results in an imbalance in the bodies in general functional activity. [33]. Many studies have shown that astaxanthin is a naturally occurring carotenoid with antioxidant properties, so the combined effect of adding astaxanthin and magnolol at different concentrations to laying hens' diets may be the cause of the significant (P ≤ 0.05) decrease in blood serum cholesterol after using natural antioxidant supplements.…”
Section: Resultsmentioning
confidence: 99%
“…The blood content of triglycerides and cholesterol is one of the important indicators that characterize the production of eggs in laying hens, and their accumulation in the blood is at high levels (higher than normal rates in the blood), It can be considered evidence of a decrease in the efficiency of using nutrients, especially fats, as a result of oxidative stress at the same time, a sharp decrease can be considered an indication of atrophy in the liver, or acute poisoning [32], This results in an imbalance in the bodies in general functional activity. [33]. Many studies have shown that astaxanthin is a naturally occurring carotenoid with antioxidant properties, so the combined effect of adding astaxanthin and magnolol at different concentrations to laying hens' diets may be the cause of the significant (P ≤ 0.05) decrease in blood serum cholesterol after using natural antioxidant supplements.…”
Section: Resultsmentioning
confidence: 99%